2005
DOI: 10.1007/s10549-005-3381-1
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Effects of Surgery: Quantitative Analysis of Circulating Basic Fibroblast Growth Factor (bFGF), Vascular Endothelial Growth Factor (VEGF) and Transforming Growth Factor Beta (TGF-β) in Patients with Breast Cancer Who Underwent Limited or Extended Surgery

Abstract: Angiogenic cytokines perioperative levels could be increased on 5th day (D(+5)) by extent of surgery and should induce perioperative stimulation of residual cancer cells. A better understanding of the time interval during which the sequelae of events in wound healing occur may be the basis for defining new therapeutic strategies that can interfere with tumor outgrowth sparing wound healing processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
31
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 21 publications
(17 reference statements)
3
31
1
5
Order By: Relevance
“…Other groups have reported an additional peak or plateau of plasma VEGF around postoperative days 8 to 10, which we have not observed (19,40). The difference may relate to the extent and type of surgery in the respective studies (16) or -as suggested by one of the authors-may be due to variations in plasma preparation (19). The latter argument seems highly feasible because different methods of plasma preparation were shown to be prone to platelet contamination and degranulation (41,42), and the extended postoperative increase in plasma VEGF correlated with an increase in platelet counts and serum VEGF levels in this particular study (19).…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Other groups have reported an additional peak or plateau of plasma VEGF around postoperative days 8 to 10, which we have not observed (19,40). The difference may relate to the extent and type of surgery in the respective studies (16) or -as suggested by one of the authors-may be due to variations in plasma preparation (19). The latter argument seems highly feasible because different methods of plasma preparation were shown to be prone to platelet contamination and degranulation (41,42), and the extended postoperative increase in plasma VEGF correlated with an increase in platelet counts and serum VEGF levels in this particular study (19).…”
Section: Discussioncontrasting
confidence: 71%
“…A significant ''spillover'' to circulation is shown in an increase of plasma VEGF concentrations on postoperative days 1 to 2, which provides a limited time window for systemic investigations on the wound healing process (14). Serum measurements primarily reflect VEGF stored in and released by platelets upon serum preparation and have thus been found to mimic the initial decrease of platelet counts in hemostatic plug formation rather than the local VEGF surge in wound tissue (14,16,17). Detectable increases in serum VEGF levels have only been reported for major surgery (16,18,19), which argues for plasma analyses to investigate changes in the systemic angiogenic balance during wound healing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of investigators have noted increased serum or plasma VEGF levels during the first 8 days after resection of gastric, breast, and large bowel malignancies [14,[19][20][21][22]. A recent study assessed plasma VEGF levels preoperatively and on days 1 and 3 after open and minimally invasive colorectal resection for both benign and malignant indications as well as after gastric bypass in morbidly obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators also have noted increased postoperative blood VEGF levels during the first 8 days after surgical resection of colorectal, gastric, and breast cancers as well as after hip surgery [14,[19][20][21][22]. It is possible, although currently unproven, that increased plasma VEGF levels after surgery might encourage the growth of tumor micrometastases that persist after resection of the primary lesion.…”
mentioning
confidence: 99%